Kayak Wisconsin Door County Peninsula : bluffs, beaches, lighthouses, and shipwrecks - Smith, Babs (2014)
Discover the most dramatic bluffs, hidden beaches, historic lighthouses, and mysterious shipwrecks in Wisconsin. Door County Peninsula is a premier kayaking destination with over 300 miles of shoreline vacillating between towering bluffs to pristine sandy beaches.Be the explorer of "Deaths Door", as the turbulent waters of Lake Michigan collide with the bay of Green Bay to Washington, Plum, and Rock Island. Each fun to read day trip offers landmarks, entertaining history and local lore, nature areas, swimming beaches, and century old shipwreck locations visible from the surface.Babs Smith's circumnavigation guidebook provides all the launch sites with driving directions and GPS coordinates for day paddles that you can customize to your own desires and abilities.Whether you are a land lover looking for magnificent shore and shimmering bays, or the excitement of surfing wild waters, this lighthearted guide of Wisconsin's Door County Peninsula is for you.